2016
DOI: 10.1016/j.tim.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Household Transmission of Influenza Virus

Abstract: Human influenza viruses cause regular epidemics and occasional pandemics with a substantial public health burden. Household transmission studies have provided valuable information on the dynamics of influenza transmission. We reviewed published studies and found that once one household member is infected with influenza, the risk of infection in a household contact can be up to 38%, and the delay between onset in index and secondary cases is around 3 days. Younger age was associated with higher susceptibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
112
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 106 publications
15
112
2
Order By: Relevance
“…With a detailed dataset consisting of up to 10,000 households, the present study was able to employ a highly flexible modelling framework to explore previously used modelling assumptions in great detail. A decrease of the per-person risk of within-household infections with household size has been observed in previous studies (8); our model selection supported that this reduced effect of household contact is better characterised as a function of the total amount of contact experienced by an individual ( C k ) rather than the household size ( N ), and that the relationship follows an inverse square root law. Previous modelling studies used different frameworks to study the relationship between SITP and household composition.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…With a detailed dataset consisting of up to 10,000 households, the present study was able to employ a highly flexible modelling framework to explore previously used modelling assumptions in great detail. A decrease of the per-person risk of within-household infections with household size has been observed in previous studies (8); our model selection supported that this reduced effect of household contact is better characterised as a function of the total amount of contact experienced by an individual ( C k ) rather than the household size ( N ), and that the relationship follows an inverse square root law. Previous modelling studies used different frameworks to study the relationship between SITP and household composition.…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, children may exhibit lower susceptibility if the vaccine uptake for them is higher than adults. The majority of household transmission studies from a systematic review (8) reported significant association between susceptibility and age (although this becomes the minority when limited to the studies with PCR-confirmed cases). Our baseline model assumes that transmissibility β is identical between individuals, but in reality transmissibility might depend on the age of the susceptibles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods were used extensively to characterize the transmission of influenza in households from a powerful study design where household contacts of confirmed influenza cases are followed-up for a few weeks after symptom onset of the first case. These analyses provided key insights about the determinants of influenza transmissionsuch as estimates of the risk of household transmission, and how this varies with household size, the infectivity and susceptibility of children relative to adults, the serial interval of influenza (which is important to determine for how long cases should be isolated, to assess the impact of treatment delays on transmission or estimate other parameters such as the reproduction number), the relationship between viral shedding and infectivity, and the protective effect of baseline antibody titres [2,[22][23][24][25][26][27][28]. These methods have also been used to investigate transmission in more complex social settings such as a school [29] or a small village [30].…”
Section: Glossarymentioning
confidence: 99%